Eribulin Mesylate Targets Human Telomerase Reverse Transcriptase in Ovarian Cancer Cells - Yamaguchi, Satoko; Maida, Yoshiko; Yasukawa, Mami; Kato, Tomoyasu; Yoshida, Masayuki; Masutomi, Kenkichi (PLOS ONE, 2014)
Treatment of advanced ovarian cancer involves platinum-based chemotherapy. However, chemoresistance is a major obstacle. Cancer stem cells (CSCs) are thought to be one of the causes of chemoresistance, but the underlying mechanism remains elusive. Recently, human telomerase reverse transcriptase (hTERT) has been reported to promote CSC-like traits. In this study, we found that a mitotic inhibitor, eribulin mesylate (eribulin), effectively inhibited growth of platinum-resistant ovarian cancer cell lines. Eribulin-sensitive cells showed a higher efficiency for sphere formation, suggesting that these cells possess an enhanced CSC-like phenotype. Moreover, these cells expressed a higher level of hTERT, and suppression of hTERT expression by siRNA resulted in decreased sensitivity to eribulin, suggesting that hTERT may be a target for eribulin. Indeed, we found that eribulin directly inhibited RNA-dependent RNA polymerase (RdRP) activity, but not telomerase activity of hTERT in vitro. We propose that eribulin targets the RdRP activity of hTERT and may be an effective therapeutic option for CSCs. Furthermore, hTERT may be a useful biomarker to predict clinical responses to eribulin.